Tan Sri Dato’ Sri Abdul Aziz Abdul Rahman appointed as Chairman, Board of Directors UMP - Siti Nur Azwin, Zulkapri (2020)
Pekan, 26 October 2020 - Tan Sri Dato' Sri Abdul Aziz Abdul Rahman was appointed as the new Chairman of the Board of Directors, Universiti Malaysia Pahang (UMP) for three years effective from 19 October 2020 to 18 October 2023.